Uso de Trichoderma nativo de Misiones para la producción de plantines de Pensamiento - Haussecker, Ricardo Daniel; Schmid, Patricia Griselda; Karlanian, Monica; Barbaro, Lorena Alejandra (Asociación Argentina de Horticultura (ASAHo), 2024)
Póster